Pelatihan Pembuatan Informasi Nomor Lagu Gereja Santo Yoseph Ngrejo Kluwut Wonosari Malang - Agus Pracoyo; Hari Kurnia Safitri; Imam Saukani; Achmad Komarudin; Edi Sulistio Budi; Agus Sukoco Heru Sumarno (P3M Politeknik Negeri Malang, 2022)
Ngrejo Hamlet, Kluwut Village, Wonosari District is located at the foot of Gunung Kawi, Malang Regency, which has relatively cold temperatures ranging from 250-350 with an area of 4331.55 km2. Kluwut Village has ethnic, racial and religious diversity. St. Joseph's Church is a place of worship for Catholics which has a very large congregation. Each service the pastor will guide the congregation to sing the songs in the worship book. With a large number of songs, the order of the songs sung will usually change at every service, so that it will be easier for the congregation to find the song page. With this problem in mind, the plan of the PPM busting team is in the form of: (1) Training on making 7 segment displays as song numbers (pages of worship books), (2) training on installation of 7 segment display devices that can be controlled remotely. It is hoped that this training can be useful for the management and congregation of the St. Joseph church. With this 7 segment display as song number information, it will be easier for the congregation to find the song page by looking at the information on the display.